2020
DOI: 10.1007/s12185-020-02930-w
|View full text |Cite
|
Sign up to set email alerts
|

Changes of hematological and immunological parameters in COVID-19 patients

Abstract: The aim of this study was to identify the changes of hematologic and immunological parameters in COVID-19 patients. We collected and analyzed the data of 117 patients who were laboratory confirmed as SARS-CoV-2 infection. The cases were divided into regular group, severe group and critically ill group according to the sixth edition scheme for COVID-19 diagnosis and treatment of China. The laboratory tests included blood routine, cellular and humoral immunity indices, biochemical detections and inflammatory bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
119
6
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(153 citation statements)
references
References 20 publications
24
119
6
4
Order By: Relevance
“…WBC, NEU, P-LCR, d-NLR, NLR, AST, urea, CK-MB and procalcitonin values were higher in the ICU group when compared to the non-ICU group, whereas LYM, eosinophil, RBC, hemoglobin, LMR and eGFR were lower. Previous studies also obtained similar results when compared with critically ill patients and regular patients [19,22]. While lymphocyte was low in 57.5% of patients in the ICU group, only 8.7% in the non-ICU group suggested that lymphopenia was an important indicator of poor prognosis.…”
Section: Median (Iqr)supporting
confidence: 71%
“…WBC, NEU, P-LCR, d-NLR, NLR, AST, urea, CK-MB and procalcitonin values were higher in the ICU group when compared to the non-ICU group, whereas LYM, eosinophil, RBC, hemoglobin, LMR and eGFR were lower. Previous studies also obtained similar results when compared with critically ill patients and regular patients [19,22]. While lymphocyte was low in 57.5% of patients in the ICU group, only 8.7% in the non-ICU group suggested that lymphopenia was an important indicator of poor prognosis.…”
Section: Median (Iqr)supporting
confidence: 71%
“… 25 Previous studies reported significantly higher ESR values in severe and critically ill patients than those in mild and moderately ill patients. 26 , 27 The higher ESR values in our symptomatic patients suggested that the inflammatory response was more prominent in them than in the asymptomatic patients. This also was supported by the longer infection period found in symptomatic than in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 72%
“…Lymphocytes are known to decrease in particularly severe cases of COVID-19 [ 1 , 57 , 58 ]. Both CD4- and CD8-positive cells are decreased, and a strong correlation exists between lymphocyte count and CD4-positive cells [ 57 , 59 ].…”
Section: Decreased Platelet and Lymphocyte Countsmentioning
confidence: 99%
“…These changes are associated with disease severity, and thus should be kept in mind during the development of future treatments. Some studies have suggested that the neutrophil-to-lymphocyte ratio is associated with the severity and prognosis of COVID-19 [ 58 , 60 , 61 ].…”
Section: Decreased Platelet and Lymphocyte Countsmentioning
confidence: 99%